Peran Kepemimpinan dalam Meningkatkan Komitmen Organisasi: Penelitian - Dicky Edwar Daulay; Maichel Jhosua; Raihan Amin Harahap (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the role of leadership in enhancing organizational commitment through an in-depth review of the literature and previous research. The primary focus of this study is on how leadership styles, particularly transformational and democratic leadership, contribute to strengthening affective, normative, and ongoing commitment within organizations. The research method used a qualitative descriptive approach utilizing secondary data in the form of scientific books, journal articles, and other relevant sources. The results indicate that leadership has a significant influence on the formation of organizational commitment, particularly through emotional support, effective communication, inspiration, and employee involvement in the decision-making process. Adaptive, communicative leaders who are able to create a positive work culture have been shown to increase employee loyalty, sense of belonging, and intrinsic motivation. Conversely, authoritarian or less responsive leadership can weaken the engagement of organizational members. This study concludes that developing leadership capacity, strengthening interpersonal communication, and creating a conducive organizational culture are important factors in increasing sustainable organizational commitment.